Plasma copper and the risk of first stroke in hypertensive patients: a nested case-control study. Issue 1 (4th June 2019) - Zhang, Jingping; Cao, Jingjing; Zhang, Hao; Jiang, Chongfei; Lin, Tengfei; Zhou, Ziyi; Song, Yun; Li, Youbao; Liu, Chengzhang; Liu, Lishun; Wang, Binyan; Tang, Genfu; et al.
ABSTRACT: Background: Previous studies indicated that trace elements may play an important role in cardiovascular diseases. However, data concerning the association between blood copper and the risk of stroke are limited. Objective: The aim of this study was to evaluate the association between plasma copper and the risk of first stroke, and examine any possible effect modifiers in hypertensive patients. Methods: We conducted a nested case-control study, using data from the China Stroke Primary Prevention Trial. Hypertension is defined as systolic blood pressure ≥ 140 mm Hg or diastolic blood pressure ≥ 90 mm Hg, or taking antihypertensive medication. A total of 618 first stroke cases and 618 controls matched for age, sex, treatment group, and study site were included in this study. The crude and adjusted risks of first stroke were estimated by ORs and 95% CIs using conditional logistic regression, without or with adjusting for pertinent covariates, respectively. Results: There were significant positive associations of plasma copper with risk of first stroke (per SD increment—OR: 1.20; 95% CI: 1.03, 1.39) and first ischemic stroke (OR: 1.26; 95% CI: 1.07, 1.50). When plasma copper was categorized in quartiles, significantly higher risks of first stroke (OR: 1.72; 95% CI: 1.12, 2.65) and first ischemic stroke (OR: 1.91; 95% CI: 1.18, 3.11) were found in participants in quartile 4 (≥ 117.0 μg/dL) than in those in quartile 1 (< 91.2 μg/dL). Furthermore, the plasma copper–first stroke association was significantly stronger in participants with higher BMI (< 25.0 compared with ≥ 25.0 kg/m 2, P -interaction = 0.024). However, there was no significant association between plasma copper and first hemorrhagic stroke. Conclusions: In Chinese hypertensive patients, there was a significant positive association between baseline plasma copper and the risk of first stroke, especially among those with higher BMI. This trial was registered at clinicaltrials.gov as NCT00794885.